2015
DOI: 10.1016/j.neuron.2015.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal 16p11.2 Protein Network Implicates Cortical Late Mid-Fetal Brain Development and KCTD13-Cul3-RhoA Pathway in Psychiatric Diseases

Abstract: Summary Psychiatric disorders autism and schizophrenia have a strong genetic component, and copy number variants (CNVs) are firmly implicated. Recurrent deletions and duplications of chromosome 16p11.2 confer high risk for both diseases, but the pathways disrupted by this CNV are poorly defined. Here we investigate the dynamics of 16p11.2 network by integrating physical interactions of 16p11.2 proteins with spatio-temporal gene expression from developing human brain. We observe profound changes in protein inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
170
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 150 publications
(180 citation statements)
references
References 64 publications
9
170
1
Order By: Relevance
“…These data suggest a model wherein KCTD13, probably in coordination with the E3 ubiquitin ligase CUL3 (refs 9, 15, 29), regulates levels of RhoA in post-mitotic neurons to modulate synaptic transmission (Extended Data Fig. 2e).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…These data suggest a model wherein KCTD13, probably in coordination with the E3 ubiquitin ligase CUL3 (refs 9, 15, 29), regulates levels of RhoA in post-mitotic neurons to modulate synaptic transmission (Extended Data Fig. 2e).…”
mentioning
confidence: 75%
“…Of many 16p11.2 genes, Kctd13 has been implicated as a major driver of neurodevelopmental phenotypes 8,9 . The function of KCTD13 in the mammalian brain, however, remains unknown.…”
mentioning
confidence: 99%
“…Causal etiological mechanisms may be overlapping or distinct from our findings. For example, a network analysis study that found that dysregulation of the KCTD13-Cul3-RhoA pathway in layer 4 of the inner cortical plate may be a potential determinant of 16p11.2 CNV brain size and connectivity phenotypes (46). Another important point to make is that networks that control dendrites may be similar, overlapping, or different from networks controlling other phenotypes, such as head size.…”
Section: Discussionmentioning
confidence: 99%
“…Rac1 is also downregulated in patients with major depressive disorder and in mice subjected to chronic social defeat, resulting in depression-related behaviors and abnormal spine remodeling [17]. Dysregulated RhoA signaling is likewise implicated in neurodevelopmental disorders associated with autism [18, 19]. Although precise spatiotemporal regulation of Rho-GTPase signaling is necessary for formation and maintenance of functional synapses, little is known about how this is achieved.…”
Section: Introductionmentioning
confidence: 99%